The evaluation of third party hotel booking website performance using Analytic Hierarchy Process (AHP) - Ramlan, Rohaizan; Hassan, Rohayanti; Mohd Shukri, Siti Rokhmah; Mokhtar, Rashidah; Tong, Bao Yee (JARDCS, 2018)
Internet has become the best source for the travellers for searching the lowest rates of hotel rooms and they are more preferred to use third party hotel booking websites to book hotel rather than using the hotel websites. This is due to third party hotel booking website can provide price and hotel’s condition comparison across multiple hotel for the customers. Since the issues of website’s qualityare critical in designing commercial websites, this research is to evaluate the third party hotel booking website that provides the important criteria and has best performance. Various web diagnostic tools are used in order to collect the primary data based on the identified criteria. The Analytic Hierarchy Process (AHP) approach is used to rank the results, based on the score achieved. It shows that the criterion of design optimisationis important in developing website and Booking.comis the best performance among third party hotel booking website. Thus, the website developer of third party hotel booking agent should more focus on the criterion of design optimisation when create their business website.